AN ANALYSIS OF CODE-SWITCHING IN GRACE TAHIR AND MERRY RIANA'S UTTERANCES ON MERRY RIANA'S PODCAST - Lusy Agnesia Sitanggang; Lisbeth Juliana Sidauruk; Enmia Virnanda Munte; Christine L.Tobing; Evelyn Zebua; Meisuri. S. A., Ginting (International Journal of Teaching and Learning, 2024)
The majority of Indonesian public figures speak both Indonesian and English, which contributes to the problem of code-switching.In order to better understand the phenomenon of code switching, this study looked at the various forms and justifications for its use by Merry Riana and Grace Tahir on their November 19, 2021, YouTube channel, "Bukan Uang, Ternyata Ini Masalah Orang Kaya -Grace Tahir (Zero To Hero Full Version)". The present study adopted a qualitative descriptive methodology, which was interpreted in accordance with a theory put forward by Appel and Muysken (1987) regarding the types of code-switching and in accordance with Hoffman's (1991: 115) regarding the reasons for code-switching.The study found all types of code-switching, as well as five reasons why code-switching occurs. First, three types of code-switching were found: tag switching (8%), intersentential switching (32%), and intrasentential switching (60%), with intrasentential switching being the most dominant. Second, five reasons why code-switching occurs were found: talking about a particular topic, being emphatic about something, the intention of clarifying the speech content for the interlocutor, quoting somebody else, and interjection. Being emphatic about something is the most dominant.